Spatial traffic estimation and characterization for mobile communication network design. - Tutschku, K. (IEEE Journal on selected areas in communications)
This paper presents a new method for the estimation and characterization of the expected teletraffic in mobile communication networks. The method considers the teletraffic from the network viewpoint. The traffic estimation is based on the geographic traffic model, which obeys the geographical and demographical factors for the demand for mobile communication services. For the spatial teletraffic characterization, a novel representation technique is introduced which uses the notion of discrete demand nodes. We show how the information in geographical information systems can be used to estimate the teletraffic demand in an early phase of the network design process. Additionally, we outline how the discrete demand node representation facilitates the application of demand-based automatic mobile network design algorithms